Average Error: 0.0 → 0.0
Time: 13.1s
Precision: 64
$\frac{\frac{x}{x - 1}}{x - 2}$
$\frac{x \cdot \frac{1}{x - 1}}{x - 2}$
\frac{\frac{x}{x - 1}}{x - 2}
\frac{x \cdot \frac{1}{x - 1}}{x - 2}
double f(double x) {
double r1523852 = x;
double r1523853 = 1.0;
double r1523854 = r1523852 - r1523853;
double r1523855 = r1523852 / r1523854;
double r1523856 = 2.0;
double r1523857 = r1523852 - r1523856;
double r1523858 = r1523855 / r1523857;
return r1523858;
}


double f(double x) {
double r1523859 = x;
double r1523860 = 1.0;
double r1523861 = 1.0;
double r1523862 = r1523859 - r1523861;
double r1523863 = r1523860 / r1523862;
double r1523864 = r1523859 * r1523863;
double r1523865 = 2.0;
double r1523866 = r1523859 - r1523865;
double r1523867 = r1523864 / r1523866;
return r1523867;
}



# Try it out

Results

 In Out
Enter valid numbers for all inputs

# Derivation

1. Initial program 0.0

$\frac{\frac{x}{x - 1}}{x - 2}$
2. Using strategy rm
3. Applied div-inv0.0

$\leadsto \frac{\color{blue}{x \cdot \frac{1}{x - 1}}}{x - 2}$
4. Final simplification0.0

$\leadsto \frac{x \cdot \frac{1}{x - 1}}{x - 2}$

# Reproduce

herbie shell --seed 1
(FPCore (x)
:name "(x/(x-1)/(x-2))"
:precision binary64
(/ (/ x (- x 1)) (- x 2)))